Data acquisition process in optical tomography : signal sample and hold circuit - Abdul Rahim, Ruzairi; Leong, L. C.; Chan, Kok San; Pang, J. F. (2005)
This paper describes the application and construction of signal sample and hold (S/H) circuit to facilitate data acquisition process using the Keithley Metrabyte DAS 1802HC. A basic tomographic system consists of sensors, signal conditioning circuit, data acquisition system and the creation of suitable computer software to display the reconstructed image obtained from pipeline. The analogue signals, which are also the data needed for image reconstruction have to be managed properly, in terms of minimizing the data transfer time from the signal conditioning circuit to the data acquisition card. Besides having a “DC memory” characteristic which can easily be converted into digital format, the sample and hold circuit also has the ability of sampling a segment of waveform and holding it until the proper timing for conversion of the required control signal. In order to generate the relevant signals to control both the signal sample and hold circuit and the data acquisition card, the PIC microcontroller is being used. With the combination of signal sample and hold circuit and microcontroller, transition of analogue signals to the data acquisition system can be performed efficiently